2023
DOI: 10.21203/rs.3.rs-2539466/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A global virome of methanogenic archaea highlights novel diversity and adaptations to the gut environment

Abstract: Mobile genetic elements (MGEs), especially viruses, have a major impact on microbial communities. Methanogenic archaea play key environmental and economical roles, being the main producers of methane -a potent greenhouse gas and an energy source. They are widespread in diverse anoxic artificial and natural environments, including animal gut microbiomes. However, their viruses remain vastly unknown. Here, we carried out a global investigation of MGEs in 3436 genomes and metagenome-assembled genomes covering all… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 135 publications
0
2
0
Order By: Relevance
“…However, our inability to detect them in other environments could be caused by the low sequence similarity values ( S1 Fig ) and the dramatic variation in gene content among pleolipoviruses. Additionally, recent work has suggested that some pleolipo-like viruses could be part of the human gut virome of methanogenic archaea [ 22 ], further expanding their habitat distribution and suggesting that the relevance of this virus group might be underestimated.…”
Section: Resultsmentioning
confidence: 99%
“…However, our inability to detect them in other environments could be caused by the low sequence similarity values ( S1 Fig ) and the dramatic variation in gene content among pleolipoviruses. Additionally, recent work has suggested that some pleolipo-like viruses could be part of the human gut virome of methanogenic archaea [ 22 ], further expanding their habitat distribution and suggesting that the relevance of this virus group might be underestimated.…”
Section: Resultsmentioning
confidence: 99%
“…6A), all belonging to the class Caudoviricetes (phylum Uroviricota), the dominant group of prokaryotic viruses. To further expand the reach of the homology detection, we searched the translated reads against the proteomes of viruses from the IMG/VR included in our database as well as a curated collection of mobile genetic elements (MGE) associated with methanogenic archaea 65 . After the search step, we identified which of the proteins have a higher likelihood to be present in a sample, and then selected those genomes that have over 20% of their proteins detected.…”
Section: Microbial Carbon Processingmentioning
confidence: 99%